Comparing migraine with and without aura to healthy controls using RNA sequencing. (October 2019) - Kogelman, Lisette JA; Falkenberg, Katrine; Halldorsson, Gisli H; Poulsen, Lau U; Worm, Jacob; Ingason, Andres; Stefansson, Hreinn; Stefansson, Kari; Hansen, Thomas F; Olesen, Jes
Background: Migraine mechanisms are*These authors contributed equally to this work. only partly known. Some studies have previously described genes differentially expressed between blood from migraineurs and controls. The objective of this study was to describe gene expression in subtypes of migraine outside of attack and in healthy controls. Methods: We extensively phenotyped 17 migraine without aura and nine migraine with aura female patients, and 20 age-matched female controls. Cubital venous blood was RNA sequenced. Genes differentially expressed between migraineurs (migraine without aura and migraine with aura) and controls, and between migraine without aura and migraine with aura were identified using a case-control design. A co-expression network was constructed to investigate the difference between migraineurs and healthy controls at the network level. Results: We found two differentially expressed genes: NMNAT2 and RETN . Both were differentially expressed between migraine with aura and controls, but they could not be replicated in an independent cohort. Co-expression network analysis resulted in one cluster of highly interconnected genes that was nominally significantly associated with migraine; however, no pathways or gene ontology terms were detected. Conclusions: We showed no clear distinct difference in gene expression profiles of peripheral blood of migraineurs and controls and were not able to replicate findings from previous studies. A larger sample size may be needed to detect minor differences.